Adrenal crisis mainly manifested as recurrent syncope secondary to tislelizumab: a case report and literature review - Wei, Haishan; Zuo, Anju; Chen, Jiying; Zheng, Chunyan; Li, Tingting; Yu, Haiyan; Guo, Yuan (Frontiers in Immunology, 2024)
As immune checkpoint inhibitors (ICIs), Tislelizumab is an anti-programmed cell death protein 1 (PD-1) drug. With the extensive application of ICIs, there is an ever-increasing proportion of immune-related adverse events (irAEs) in clinic, some of which may even be life-threatening.Herein we present a patient of Tislelizumab-induced adrenal crisis. The main clinical manifestation is recurrent syncope accompanied by high-grade fever. Timely identification and hormone replacement therapy helped the patient get through the crisis well. Finally,the patient discontinued Tislelizumab and switch to ADC therapy. We reported this case to improve our understanding of this situation, identify this kind of disease and prevent adrenal crisis in time.Eventually, limiting toxicities to reduce the interruption of immunotherapy. Since irAEs are multisystem damage with more non-specific symptoms, except for oncologists, general practitioners who endorse the need for taking a holistic approach to the patient should play a vital role in the management of cancer treatment.